2016
DOI: 10.1111/jfd.12587
|View full text |Cite
|
Sign up to set email alerts
|

Selective precipitation reaction: a novel diagnostic test for tissue pathology in Atlantic salmon, Salmo salar, infected with salmonid alphavirus (SAV3)

Abstract: While investigating biomarkers for infection with salmonid alphavirus (SAV), the cause of pancreas disease (PD), a selective precipitation reaction (SPR) has been discovered in serum which could be an on‐farm qualitative test and an in‐laboratory quantitative assay for health assessments in aquaculture. Mixing serum from Atlantic salmon, Salmo salar, with SAV infection with a sodium acetate buffer caused a visible precipitation which does not occur with serum from healthy salmon. Proteomic examination of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Some of the fish viruses that have been detected by ELISA include VHSV in rainbow trout Oncorhynchus mykiss (Olesen, Lorenzen, & Jørgensen, ), Koi herpesvirus (KHV) in koi or coloured carp ( Cyprinus carpio )(Adkison, Gilad, & Hedrick, ) and nervous necrosis virus (NNV) in barramundi Lates calcarifer (Jaramillo, Hick, Dyrting, Anderson, & Whittington, ). More recently, a field‐deployable novel selective precipitation reaction (SPR) was discovered that could be used to detect salmonid alphavirus (SAV) using serum, making it an attractive serological method (Braceland et al, ). However, more research needs to be done on its applicability to other viruses including TiLV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the fish viruses that have been detected by ELISA include VHSV in rainbow trout Oncorhynchus mykiss (Olesen, Lorenzen, & Jørgensen, ), Koi herpesvirus (KHV) in koi or coloured carp ( Cyprinus carpio )(Adkison, Gilad, & Hedrick, ) and nervous necrosis virus (NNV) in barramundi Lates calcarifer (Jaramillo, Hick, Dyrting, Anderson, & Whittington, ). More recently, a field‐deployable novel selective precipitation reaction (SPR) was discovered that could be used to detect salmonid alphavirus (SAV) using serum, making it an attractive serological method (Braceland et al, ). However, more research needs to be done on its applicability to other viruses including TiLV.…”
Section: Discussionmentioning
confidence: 99%
“…was discovered that could be used to detect salmonid alphavirus (SAV) using serum, making it an attractive serological method (Braceland et al, 2017). However, more research needs to be done on its applicability to other viruses including TiLV.…”
Section: Discussionmentioning
confidence: 99%
“…Braceland et al . ( 7 ) have also identified and validated a novel selective precipitation reaction (SPR), establishing a procedure which can be used to monitor the health of farmed Atlantic salmon. The study has demonstrated that the assay is rapid, sensitive, and practical for daily operations.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…These include real-time RT-PCR, conventional RT-PCR (with sequencing for genotyping), immunohistochemistry, histopathology, serum neutralization assay, and isolation of virus in cell culture. A serum-based selective precipitation reaction (SPR) has also been recently described (21), however this is currently not in use in Norway and is not listed on the OIE disease card.…”
Section: Introductionmentioning
confidence: 99%